COMPARATIVE ANALYSIS OF THE LAWNS STRUCTURE ALONG BELGRADE CITY ROADS - Stavretović, Nenad; Novaković , Ana; Petrović , Jovana; Stojanović , Nadežda (Acta herbologica, 2022)
The research includes a comparative analysis of the structure of different types of lawns along Belgrade roads (grass areas of roundabouts, dividing strips, areas near roads and grass areas of first order roads), their floristic composition, as well as determining changes over a period of 17 years. The analyzes used the results of floristic research from 2002, as well as the results of field research conducted during 2019. A total of 114 plant species were recorded on the investigated lawns along Belgrade’s roads, among which the largest number belongs to the category of weed species. It has been shown that there are no significant changes in terms of taxonomic analyzes of lawns in the studied period. An important difference occurs in the number of blunted families and genera, which were more at the beginning of the research period. Both studies indicate the absolute dominance of plants from the group of hemicryptophytes. The results of the research are used to provide guidelines and recommendations for improving the condition and structure of lawns along Belgrade’s roads. Also, they form the basis for the future selection of adequate types of grass for the establishment of new ones as well as the repair of existing lawns, ie in a broader sense for sustainable management of green spaces along city roads.